Multivariate analysis of correlates of children nutritional status in Harar region, Ethiopia - Kebede, Dufera Tejjeba; Bekalo, Daniel Biftu; Mekuriaw, Daniel Mesele (International Journal of Scientific Reports, 2020)
Background: Malnutrition is defined as deficiencies, excesses or imbalances in a person’s intake of energy and/or nutrients. In Ethiopia malnutrition is one of the most serious health and welfare problems among infants and young children. Malnutrition among children under five years of age is a chronic problem in most regions of Ethiopia, including the Harari region. The main objective of this study was to assess risk factors attributed to nutritional status of children in Harari region. Methods: Data was obtained from Ethiopian Demographic Health Survey, 2016. Different factors were considered as determinants of nutritional status of a child. The study used Multivariate Multiple Linear Regression model to identify significant correlates of children nutritional status. Results: The descriptive statistics in the study revealed that out of a total of 233 children included in the study 21% are underweighted, 19.3% are stunted and 11.2% are wasted in the study area. From Multivariate multiple linear regression, breast feeding factors, health status of child and child vaccination status significantly affect nutritional status of the under five children. Conclusions: The factor analyses conducted in this study indicated that only two factors (instead of 5 original observed variables or items) were sufficient to explain 78.605% of the total variation in PCFA of observed items related to child nutritional status. Factors duration of breast feeding, birth order of a child, current age of child is statistically significant in affecting child malnutrition.